Elan Corporation turnaround - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
The case begins with newly appointed chairman and interim CEO Garo Armen dwelling on the significant issues that Elan Corporation, an Irish pharmaceutical company, faces. Its share price has plummeted 96% after accusations of accounting fraud and the discontinuation of an important clinical trial due to the drug's severe side effects. As a result, Elan faces insolvency. About $2 billion in debt that could no longer be satisfied in stock will soon mature, and there are questions regarding the company's structure and various operating concerns.